Microprocessor Solder Bump Bridging Defects Screening Strategy In Manufacturing Test Flow - Loo , Kean Ann (2017)
Solder bump bridging (SBB) is a type microprocessor packaging defects in Flip-Chip or C4 interconnection layer. The presence of micro conductive contaminate particle in die-package layer which causes bridging between two or more adjacent solder bump. These contaminate particles are mainly comes from solder bump fraction result from deficient packaging process. Today semiconductor manufacturing test flow is still imperfect to completely screen or detect the SBB defect. As bounce back, the test holes contributes to the defect per million (DPM) of the product. In this research, the test holes of SBB defect in High Volume Manufacturing (HVM) will be defined. Meanwhile, SBB defect characterization will be studied where the electrical behavioural of baby bumps is explained. In the final part of the study, an effective SBB screening test at Burn In is developed to minimizing test holes. From the research finding, un-bridging of SBB occurs at extreme high current of 4.5 A where the baby bump burnt and partial unbridged. This unbridged state are unstable and lacking in term of reliability. However, the SBB un-bridging only impacted on Type B SBB defect where baby bump bridging power bump with ground bump. Lastly, the SBB screening test at Burn In stage is developed as part of this research. In conclusion, the proposed test has the potential in minimizing HVM SBB defect test holes by improving SBB defect fault coverage.